The choice of civil war. Another history of neoliberalism - Zanotelli, Cláudio Luiz (Geografares, 2021)
Innovative book in the approach on a major theme that is the association between neoliberalism and reactionarism, between neoliberalism and "civil war" of governments against citizens. Two of the authors have previously published in Brazil by Boitempo: Pierre Dardot and Christian Laval, The new reason of the world. Essay on neoliberal society (2016); Common. Essay on revolution in the 21st century (2017). And by the Publisher Perspective The Shadow of October: The Russian Revolution and the Specter of the Soviets (2018). Christian Laval published in Brazil by Editora Elefante the book Foucault, Bourdieu and the neoliberal question in 2020.
Keywords: book review; neoliberalism; The choice of civil war